The effect of competence and self-leadership on the organizational commitment of assessors of P1 professional certification institutions (LSP-P1) in Indonesia - Susanti, Nurul Indah; Brahmasari, Ida Aju; Suryani, Tatik (International research journal of management, IT and social sciences, 2022)
The purpose of this study was to analyze the effect of competence and self-leadership on the organizational commitment of Assessors of P1 Professional Certification Institutions (LSP-P1) in Indonesia. The object of this research is the P1 Professional Certification Institute (LSP-P1) in Universities and Vocational Schools in Indonesia with a population of 26,021 P1 assessors in Indonesia obtained from the 2019 BNSP report, while the sample taken is 393.94 rounded up to 400 assessors calculated with Slovin's formula. Data was collected using a survey method with a questionnaire instrument, while the analysis technique used was Structural Equation Modeling (SEM) through Amos. The results showed that competence had a significant effect on organizational commitment and self-leadership had a significant effect on organizational commitment. Based on the results of the analysis and discussion in this study, suggestions for LSP-P1 should still pay attention to several things such as technical competence can increase the assessor's organizational commitment and LSP must also support the creation of self-leadership of assessors so that they have high commitment.